(3EbGeI GdMLI aj GdQO Ydi eG CMOKJg GdeHJOYIs - (3eMeO Hf Ydj Hf GdaTJGdj GdeZQHjs
(3ChdgG (B:s
(3CeG HYO abO SCdfi HYV CNhGffG Gf CcJH dge s
(3BNQgG (B:s
(3hXghQ GdefRdI YfO GdfGS hjJYXe ai bdhH GdCeQGA s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 152/6) s
Keywords: (3CUhd Gdabgs